The Industrial Health Hazard among Workers of Apparel Sector in Bangladesh - G. M. Faysal; T.N. Sonia Azad; Jannatul Mawa Moon (Universitas Airlangga, 2022)
Introduction: The Bangladesh's Ready-Made Garment (RMG) sector is now the world's 3rd largest exporter. RMG provides a steady flow of employment for approximately 4,000,000 workers, the majority of whom are women. This remarkable progress, however, has been hampered by a lack of factory safety and industrial mishaps, which characterize health risks. Methods: With a population of 200 employees, this was a quantitative study. Interviews with informants were conducted using an interview guideline, and observations were carried out around the workplace using a checklist instrument. The information gathered was used to create a detailed picture of the scenario. This research aims to investigate health hazards of the garment industrial workers and their effects on workers’ health. Results: The majority of garment workers were between the ages of 15 – 20 years old. 93.6% of respondents worked for 8 - 9 hours each day on average, and 79.2% put in an extra 2-4 hours of work. 66% had no accident in the previous year, while 24.7 % experienced a small cut, abrasion, or injury. Moreover, most respondents were unconcerned about physical or environmental pollution, while 68% were concerned about noise pollution. Due to the direct link to health risks, employees suffered from headaches, general weakness, and eyestrain. Conclusion: Workers’ headaches and eyestrain were caused by an insufficient lighting and ventilation system and noise pollution. Backaches, joint pain, and chest pain were caused by long working hours and a dirty workplace. Industrial health hazards should be minimized by the proper implementation of labor laws by the government. Keywords: hazard, illness, ready-made garment, ready-made garment worker, safety